Konsep Syukur dalam Al-Quran dan Hadis Perspektif Psikologi Islam - Wantini Wantini; Ricki Yakup (Jurnal Studia Insania, 2023)
The failure of people to interpret life is the reason for their inability to be grateful for their lives. The purpose of this study is to find the concept of gratitude in the Quran and hadith in the perspective of Islamic Psychology studies. This research is included in the type of literature research or commonly called Library Research, because the data studied is in the form of books sourced from literature treasures. The results of this study found that the concept of gratitude in the Quran and Hadith from the perspective of Islamic Psychology there are three main concepts, namely the concept of gratitude with the heart, the concept of gratitude verbally and the concept of gratitude with deeds. There are several concepts of gratitude in the Quran and hadith in the perspective of Islamic Psychological studies: First, Surat al-Ankabut verse 45 and Bukhari's hadith on mindfulness. Second, Surah Ibrahim verse 7 and Abu Hurayrah's hadith about gratitude journaling. Third, Surah An-Naml verse 93 and Hadith Muslim Narration about the relationship with mental health. Fourth, An-Nahl verse 53 and the hadith of Abu Hurairah (r.a) on religiosity and coping.